The neurobiology of language: Relevance to linguistics - Duncan, E. Susan; Tune, Sarah; Small, Steven L. (Yearbook of the Poznan Linguistic Meeting, 2016)
The study of language is shared by a number of fields, including linguistics, psychology, and neurobiology. While the methods employed by these domains may overlap, they differ in the focus of their scientific inquiry, and the unique perspective of each may inform investigation within the others. We conceptualize this relationship in the context of David Marr’s information processing theory, with neurobiology as the implementational level of language, and discuss the history of the neurobiology of language from early localizationist models to the present day. Decades of electrophysiological and anatomical studies of the macaque monkey support the existence of dual streams for the processing of auditory information. More recent neuroimaging studies suggest that these streams are also present in humans, subserving speech perception and language comprehension. The development of high resolution brain imaging methods and brain stimulation has advanced our ability to study, in vivo, the structures and processes underlying the language network. For those linguists interested in studying language with consideration of the system that implements it, theories and concepts may now be meaningfully informed by neurobiology.